3D modeling and printing with Tinkercad : create and print your own 3D models / James F Kelly - Kelly, James F. (James Floyd)
Want to master 3D modeling and printing? Tinkercad is the perfect software for you: it's friendly, web-based, and free. Even better, you don't have to rely on Tinkercad's technical documentation to use it. This guide is packed with photos and projects that bring 3D modeling to life!